2017
DOI: 10.1149/2.0781706jes
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemical Sensing Platform for Carbamazepine Determination Based on Trimetallic Au-Ag-Pd Dendritic Nanopatricles, Supramolecular β-cyclodextrin and [bmim] NTF2 Ionic Liquids

Abstract: A novel electrochemical sensor was constructed for sensitive and selective determination of carbamazepine (CBZ). First trimetallic Au core AgPd shell nanoparticles (Au@AgPdNPs) with dendritic morphology were synthesized by a facile method and then the nanocomposite of Au@AgPdNPs, macrocyclic β-cyclodextrin and butyl-3-metylimidazolium bis (trifluorometylsulfonyl) imide ionic liquid was prepared to modify a glassy carbon electrode. The formation of Au@AgPdNPs was characterized using transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Similarly, various metal nanoparticles have been combined with CDs to form decorated glassy carbon electrodes. For example, Daneshvar and Rounaghi [156] employed trimetallic Au/Ag/Pd nanoparticles with β-CD for the detection of carbamazepine. Similarly, a number of carbon paste electrodes modified with metal nanoparticles and β-CD have been formed and utilized as electrochemical sensors and this includes gold [157,158] and platinum nanoparticles [46], while gold substrate electrodes have been modified with gold nanoparticles, β-CD, and Nafion [159].…”
Section: Other Conducting Materials Combined With Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, various metal nanoparticles have been combined with CDs to form decorated glassy carbon electrodes. For example, Daneshvar and Rounaghi [156] employed trimetallic Au/Ag/Pd nanoparticles with β-CD for the detection of carbamazepine. Similarly, a number of carbon paste electrodes modified with metal nanoparticles and β-CD have been formed and utilized as electrochemical sensors and this includes gold [157,158] and platinum nanoparticles [46], while gold substrate electrodes have been modified with gold nanoparticles, β-CD, and Nafion [159].…”
Section: Other Conducting Materials Combined With Cyclodextrinsmentioning
confidence: 99%
“…Similarly, various metal nanoparticles have been combined with CDs to form decorated glassy carbon electrodes. For example, Daneshvar and Rounaghi [156] employed trimetallic Au/Ag/Pd nanoparticles with β-CD for the detection of carbamazepine.…”
Section: Cyclodextrin-based Biosensorsmentioning
confidence: 99%
“…Also, they pointed out that the previously reported electrodes could not used for simultaneous detection. 78 Moreover, to evaluate the application possibilities of the modified electrode, different amounts of dopamine (10, 100, and 800 nM) and carbamazepine (4, 200, and 600 nM) were added to human serum for detection. From these results, they stated that the electrode was an ideal tool for the simultaneous detection of dopamine and carbamazepine in physiological samples.…”
Section: Synthesis and Applications Of Zeolite Compositesmentioning
confidence: 99%
“…They compared their results with various modified electrodes and found that the prepared electrode had the lowest detection limit. Also, they pointed out that the previously reported electrodes could not used for simultaneous detection . Moreover, to evaluate the application possibilities of the modified electrode, different amounts of dopamine (10, 100, and 800 nM) and carbamazepine (4, 200, and 600 nM) were added to human serum for detection.…”
Section: Synthesis and Applications Of Zeolite Compositesmentioning
confidence: 99%
“…8,9 Recently, several analytical techniques have been employed for the determination of CBZ level including solid phase extraction, 10 high performance liquid chromatography, 11 gas chromatography, 12 mass chromatography, 13 chemiluminescence, 14 spectrophotometry, 15 electrochemical determination. [16][17][18][19] Among these, most of the methods suffer from many issues including tedious procedure, requiring expensive instruments, long-time sample pretreatment and lack of portability. On other hand, electrochemical techniques offer a range of advantages including easy operative, rapid, accurate, high sensitivity, good selectivity, low cost, and minimal reagent consumption.…”
mentioning
confidence: 99%